Rethinking of Islamic Promotion for Halal Products within the Nationalism in the Local Genius at 6.0 Era - Mahsun, Moch; Sa’adah, Haqiqotus; Shohib, Moch (Proceedings of Annual Conference for Muslim Scholars, 2024)
This study explores the integration of Islamic values, nationalism, local cultural wisdom, and advanced technologies in promoting halal products in the 6.0 Era. By examining political, economic, social, technological, legal, and environmental factors, it highlights the role of robust government policies, ethical transparency, and digital innovations like blockchain and AI in enhancing consumer trust and market efficiency. The research underscores the significance of leveraging local genius, such as traditional art and cultural narratives, to foster authenticity and preserve heritage in halal branding. Additionally, it emphasizes eco-friendly practices in halal production, aligning with Islamic principles of stewardship and global sustainability goals. A holistic framework addressing these intersections ensures halal products remain competitive and culturally resonant while meeting evolving global demands. The findings demonstrate the potential of Islamic values to guide ethical practices and promote sustainable development in a technologically advanced and interconnected global economy.